The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4025/actascianimsci.v41i1.45666
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vinasse on the growth performance and feed digestibility of Holstein male calves

Abstract: Industrial effluents of alcohol production are problematic for the environment. One of the proposed solutions to the reduction of harmful effects of the wastewater is to convert it into vinasse. The purpose of the present study is to investigate effects of rations with different levels of vinasse as a source of protein in the diet of 28 male Holstein calves, previously health checked, with an average initial weight of 300 ± 22.56 kg and the maximum similarity of weight and age. The calves were divided randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Moharrery et al [14] reported a negative slope in increasing of daily starch intake on ruminal starch digestibility. Furthermore, vinasse-molasses is more palatable than molasses for cattle due to most of protein is combined with amide compounds [3]. In accordance with our result, Maneerat et al [7] reported that utilization of vinasse on bagasse-vinasse mixture reduce DMI of steers in compare to rice straw-molasses diet.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moharrery et al [14] reported a negative slope in increasing of daily starch intake on ruminal starch digestibility. Furthermore, vinasse-molasses is more palatable than molasses for cattle due to most of protein is combined with amide compounds [3]. In accordance with our result, Maneerat et al [7] reported that utilization of vinasse on bagasse-vinasse mixture reduce DMI of steers in compare to rice straw-molasses diet.…”
Section: Discussionsupporting
confidence: 90%
“…Parsaee et al [2] reported that vinasse contained a wide range of organic compounds including sugar and carbohydrates, organic acids, and some minerals (potassium, calcium and sulfate) which makes it potentially used as feed ingredient in animal feed. Another study reported that Vinasse-molasses contained of 20% crude protein and mineral, such as potassium (64 g/kg), sodium (19.2 g/kg), and calcium (17.5 g/kg) [3]. Thus, vinasse has a high potency to be used as an alternative to molasses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, consumption of starch poorly affected ruminal starch digestibility resulting a negative slope in daily starch intake [9]. In addition, most protein of vinasse-molasses is combined with amide compounds [10] which makes it more palatable. Vinasse-molasses did not change (P>0.05) FBW, ADG, and FE of Peranakan Ongole cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it was also reported that dietary betaine supplementation in laying quails might increase the digestibility of dry matter, crude protein, crude fiber, and crude ash, which positively affects the intestinal mineral absorption and digestive capacity of the intestinal epithelium. 28,29 Gerimipour et al 21 also reported that vinasse contained betaine and the calcium concentration of vinasse was also high. The positive effects of vinasse on mineralization was observed by Cetin et al 17 that egg shell thickness and shell breaking resistance increased in quails fed with the addition of vinasse compared to quails without vinasse, and it was reported that this positive effect may be due to the effect of betaine on the increase of mineral substance absorption in the intestines.…”
Section: Discussionmentioning
confidence: 98%
“…14 Because of these properties, beta vinasse can be considered a good source of nutrients and minerals. Moreover, the mineral content of vinasse may play a crucial role in developing the musculoskeletal system 21 , increasing bone strength, and preventing losses due to disorders related to the musculoskeletal system in laying hens. However, the effect of vinasse on bone strength in laying hens has not yet been discovered.…”
Section: Introductionmentioning
confidence: 99%